Sensitivity of Foreign Direct Investment to Macroeconomic Variables in Nigeria - Oloyede, John Adebayo; Kolapo, Funso Tajudeen (Advances in Social Sciences Research Journal, 2018)
This study investigated the sensitivity of foreign direct investment to macroeconomic variables in Nigeria for the 1986 to 2016 period. The study adopted foreign direct investment as the dependent variable, while gross domestic product, unemployment rate, inflation, government expenditure, exchange rate, interest rate, population and openness to trade were proxies for independent variables. The Ordinary Least Square (OLS) estimates revealed that inflation rate, population and openness to trade have significant positive influence on foreign direct investment, while economic growth has a negative though significant influence on FDI. Furthermore, unemployment, exchange and interest rates exert negative and insignificant influence on FDI inflows into Nigeria all in the short run. Therefore, FDI inflow to Nigeria is sensitive to changes in economic growth, inflation, population and openness to trade, hence the sensitivity of FDI to population size is of greater magnitude. From this findings, it is recommended, among other things, that the government should tackle unemployment and corruption problems frontally, while the managers of the Nigerian economy should also focus on controlling interest rate and maintaining the stability of exchange rates in order to attract, enhance and improve FDI inflows to the country.